Interpretation of Prophet Joseph's Political Strategy in the Qur'an: Leadership, Conflict Resolution, and Its Relevance to Contemporary Politics in Indonesia - Aswadi; Abdur Rohman; Ummah, M. Fijar Ishlahul; Anam, Masrul (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This article examines the political strategies of Prophet Yusuf as recorded in the Qur'an, focusing on leadership and conflict resolution, as well as their relevance to the phenomenon of dynastic politics in Indonesia. Although Muslims regard the Qur'an as a guide, their understanding of its political aspects remains limited. The story of Prophet Yusuf in Surah Yusuf offers valuable lessons on political strategies based on ethics and wisdom. This study employs a library research approach with a thematic tafsir method, analyzing various exegetical perspectives on the verses describing Yusuf's political strategies. The findings reveal that Yusuf implemented several political strategies relevant to the context of dynastic politics, namely: first, the politics of reciprocal obligation, where he repaid ill treatment with kindness to build long-term influence. Second, the politics of desire, by creating dependency so that others would follow his will. Third, the politics of scenario, which involved strategically setting situations so that opponents would accept the prevailing rules. Fourth, the politics of control, in which Yusuf carefully managed the narrative and actions of his adversaries. Fifth, the politics of identity declaration, where he revealed his true identity at the right moment to maximize acceptance. Sixth, the politics of accommodation, which ultimately led his brothers to submit and join him in Egypt. Yusuf's political strategies reflect a form of leadership that prioritizes wisdom, strategic planning, and conflict management. In the context of dynastic politics in Indonesia, similar strategies can be observed in how political elites build influence, maintain power, and manage both support and opposition. Contribution: This study contributes to understanding how Qur'anic values can serve as a reference for contemporary political analysis.